Influence of heavy rainfall in 2018-2019 and submerging on some soil properties greenhouse’s in Bazian plain, Sulaymaniyah Governorate - Akram M. Abdul Rahman; Farhad Mahmoud Tawfiq; Hassen R. Hama Amin; Awara Ahmed Abdullah; Bakhtiar Abdullah (Kufa Journal for Agricultural Sciences)
In rain season 2018-2019 Sulaymaniyah governorate has been precluded to rainfall precipitation with very high quantities that never has been recorded since 1985 that impact on some soil properties taking samples from 80 greenhouses in (Tainal watershed, Bazian plain, Sulaymaniyah Governorate). Since in some of these greenhouse waters flood get 1.5m high and others distorted and kinds of residues has been collected in others greenhouses as well as effects of water submerging on these greenhouses soils. Taking soil samples from greenhouses from all locations that effected hardly and making analysis for some properties’ as a parameters and the results showed that the soil solution electrical conductivity (EC) decreased significantly (P<0.05) in ( Location1, Location2, Location6) (1.65dsm-1,0.35dsm-1, 0.25dsm-1 ) respectively. the pH of soils decreased as the results showed (Location1, Location2, Location3) (8.06, 8.31, 7.8) respectively but not significantly, soil aggregate differences had effected significantly and changed in different locations because of removal of the sand part, silt decreased from (% 17.25) in control Location to (5.6 in Location2, 4.1in Location7) but didn’t get to the limit that could change the soil texture. Submergence soils caused decreasing significantly (P<0.05) in phosphorus concentration in (Location1, Location7) (17ppm, 12ppm) respectively. The Concentration of nitrate in soil solution decreased significantly (P<0.05) (Location1, Location7) (2.5mg kg-1, 14mg kg-1) respectively under the submerged condition at field capacity causing an increase in the concentration of potassium (0.743 in Location3 and 4.358 in Location4) in some locations. Sodium increased in most of the locations significantly (P<0.05) (L1, L3, L5, L7) (0.378m mol-1, 0.434m.mol-1, 0.443m.mol-1, 0.643 m.mol-1) respectively otherwise, magnesium and calcium decreased in the soil solution. From the investigation some farmer record that in the study area vegetables grew better after the submerging soils.